Discordant Noninvasive Prenatal Testing and Cytogenetic Results: A Study of 109 Consecutive Cases. Issue 7 (July 2015) - Wang, Jia-Chi; Sahoo, Trilochan; Schonberg, Steven; Kopita, Kimberly A.; Ross, Leslie; Patek, Kyla; Strom, Charles M.
Abstract : ABSTRACT: Cell-free DNA has been demonstrated to be incrementally valuable for noninvasive prenatal testing (NIPT) in recent studies. Noninvasive prenatal testing showed 100% sensitivity for trisomy 18 and trisomy 21 in 1 study. However, others have reported cases in which positive results were not confirmed, and this review looks to determine the concordance of positive NIPT results with cytogenetic studies. Results from 109 specimens prenatally and/or postnatally studied after NIPT were included in the study. These specimens were studied by 1 or more of the following methods: standard karyotyping, fluorescence in situ hybridization, or oligo–single-nucleotide polymorphism microarrays. Trisomy 21 was the most common initial NIPT-positive result, with 41 cases. The second most common result was trisomy 18 (25 cases), followed by trisomy 13 (16 cases), sex chromosome aneuploidy (16 cases), trisomy 16 (3 cases), monosomy 21 (2 cases), triploidy (1 case), and microdeletion of 22q11.2 (1 case). Also included were 4 NIPT-negative samples that had abnormal ultrasound findings suggestive of aneuploidy. For trisomy 21, the NIPT true-positive rate was 93%, with cytogenetic results positive in 38 of 41 NIPT-positive cases, and trisomy 18 had a true-positive rate of 64% with 16 or 25 NIPT-positive cases testing positive in cytogenetic study. For trisomy 13, the true-positive rate was 44% (7/16 cases), and for sex chromosome aneuploidy, 38% (6/16 cases). Six cases had normal cytogenetic findings following NIPT-positive results for monosomy 21, trisomy 16, triploidy, or 22q11.2 microdeletion. Positive predictive values (PPVs) were calculated using these findings as well as the findings from the 2 independent groups, showing a highest PPV by NIPT for trisomy 21 (119/126, 94.4%) and significantly lower PPV for trisomy 18 (25/42, 59.5%), trisomy 13 (12/27, 44.4%), and sex chromosome aneuploidy (11/29, 37.9%). Positive predictive value is determined by specificity of the assay, the sensitivity, and the prevalence of the abnormalities tested when NIPT is offered. The findings from this study show the necessity of cautious interpretation of NIPT results. The study also suggests the need for careful communication of those results to both patients and providers. It is important for providers to understand the difference between specificity and PPV.